2012
DOI: 10.1111/j.1468-036x.2011.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Index ETFs on Spot‐Futures Pricing and Liquidity: Evidence from the CAC 40 Index

Abstract: International audienceThis paper investigates how the introduction of an index security directly or indirectly impacts the underlying-index spot-futures pricing. Using intraday data for financial instruments related to the CAC 40 index, we do not find that the spot-futures price efficiency improvement observed after ETF introduction is explained either by the direct effect of ETF shares being used in arbitrage trades or by the indirect effect of ETF trading improving the liquidity of index stocks in the short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…The effect of ETFs on arbitrage activities in the spot and futures markets is referred to as the direct effect of ETFs, while the effect of ETFs on the respective underlying stocks' liquidity is described as the indirect effect of ETFs. While in the short term, neither direct nor indirect effect of ETFs on the price efficiency of their component stocks could be observed based on the data used in their study; however, Deville et al (2014) suggest that in the long term, the price efficiency improves, especially through the indirect effect of ETFs. 10 They suggested that the ETFs are more appealing to hedgers and liquidity traders who focus on long-term positions, but they may appear unattractive to arbitrageurs in relation to index futures.…”
Section: What Informational Role Do Etfs Play In Price Discovery? -Sumentioning
confidence: 82%
See 4 more Smart Citations
“…The effect of ETFs on arbitrage activities in the spot and futures markets is referred to as the direct effect of ETFs, while the effect of ETFs on the respective underlying stocks' liquidity is described as the indirect effect of ETFs. While in the short term, neither direct nor indirect effect of ETFs on the price efficiency of their component stocks could be observed based on the data used in their study; however, Deville et al (2014) suggest that in the long term, the price efficiency improves, especially through the indirect effect of ETFs. 10 They suggested that the ETFs are more appealing to hedgers and liquidity traders who focus on long-term positions, but they may appear unattractive to arbitrageurs in relation to index futures.…”
Section: What Informational Role Do Etfs Play In Price Discovery? -Sumentioning
confidence: 82%
“…However, Deville et al (2014) examined the direct and indirect effect of ETFs on their underlying stocks' price efficiency. The effect of ETFs on arbitrage activities in the spot and futures markets is referred to as the direct effect of ETFs, while the effect of ETFs on the respective underlying stocks' liquidity is described as the indirect effect of ETFs.…”
Section: What Informational Role Do Etfs Play In Price Discovery? -Sumentioning
confidence: 99%
See 3 more Smart Citations